Developmental reading 1 - Bernardez, Edisteo B. (Manila : Mindshapers, 2007)
This book is prepared in conformity with the measures of the course specified in the Commission on Higher Education Memorandum Order (CMO) No. 30 S. 2004.
Chapter 1: Developmental reading -- Chapter 2: How to determine the meaning of a new word by using context clues -- Chapter 3: How to conduct the silent reading exercises -- Chapter 4: Enunciation and pronunciation -- Chapter 5: Variations in the pronunciation of consonants -- Chapter 7: Intonation -- Chapter 8: How to read literary selections -- Chapter 9: Selections.
Includes bibliographical references and index.
Keywords: READING